2022
DOI: 10.1007/s00170-022-10311-2
|View full text |Cite
|
Sign up to set email alerts
|

Strengthening of duplex stainless steel processed by equal channel angular pressing (ECAP)

Abstract: This manuscript presents the study of the microstructural evolution, plastic anisotropy, and mechanical behavior of a duplex stainless steel (DSS) processed by the equal channel angular pressing (ECAP) technique. The ECAP process produced shear bands affecting both phases, austenite and ferrite, which in turns act as preferential sites for the appearance of the new ultrafine grains. Microstructural observations indicated grain sizes smaller than 300 nm in both phases. However, marked differences in the grain b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 70 publications
0
2
0
Order By: Relevance
“…In duplex steels processed by ECAP, it has been shown that the appearance of shear bands is favored because the two phases store different magnitudes of deformation, creating a heterogeneous state. In addition, during ECAP, the fraction of austenite declines gradually, and it tends to refine ferrite faster, which is attributed to the twinning deformation mechanism that favors grain fragmentation (31,61) .…”
Section: Stainless Steelmentioning
confidence: 99%
“…In duplex steels processed by ECAP, it has been shown that the appearance of shear bands is favored because the two phases store different magnitudes of deformation, creating a heterogeneous state. In addition, during ECAP, the fraction of austenite declines gradually, and it tends to refine ferrite faster, which is attributed to the twinning deformation mechanism that favors grain fragmentation (31,61) .…”
Section: Stainless Steelmentioning
confidence: 99%
“…On the other hand, metallic materials with two phases, such as duplex, dual phase, and austenitic stainless steels, present different dislocation densities due to their different capacities to distribute deformation. According to several authors [38,44,45], deformation distribution must also be heterogenous between the two phases leading to additional material hardening. It also demonstrates the creation of plastic gradients around the weld seam and between the phases of each zone.…”
Section: Microstructure Evolutionmentioning
confidence: 99%
“…The SPD implementation due to the intensification of shear and alternating strains makes it possible to achieve the refinement of the initial structure to an ultrafine-grained state and obtain unique mechanical characteristics, which are sometimes par-adoxical [4,5]. At the same time, the most well-known SPD methods-high-pressure torsion (HPT) and equal-channel angular pressing (ECAP)-allow deforming samples of limited geometric dimensions, which significantly reduces the possibility of using these methods on an industrial scale [6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%